Sistem Ekonomi Perbankan Berlandaskan Bunga (Analisis Perdebatan Bunga Bank Termasuk Riba Atau Tidak) - Abdul Haris Romdhoni; Muhammad Tho'in; Agung Wahyudi (ITB AAS INDONESIA, 2012)
Bank interest is the remuneration provided by the bank based on conventional principles to customers who buy or sell their products. Bank interest can be in the form of interest on deposits and interest on the loan. The purpose of this study is to determine the various opinions and about the interest position of usury bank or not. The research method used in this research topic is in the form of study or literature study obtained from various sources of books, journals, and other sources that are very relevant to the research topic. The results show that most scholars and scholars claim that the bank interest is the same as usury, so the law of bank interest is haram. But there is also a judge that bank interest is different from interest, so bank interest is okay, especially some Middle Eastern clerics supported by secular-minded economic experts.